Cryoglobulinemia and double‐filtration plasmapheresis: Personal experience and literature review. Issue 1 (28th May 2022) - Naciri Bennani, Hamza; Banza, Augustin Twite; Terrec, Florian; Noble, Johan; Jouve, Thomas; Motte, Lionel; Malvezzi, Paolo; Rostaing, Lionel
Abstract: Background: Cryoglobulinemia is defined as the presence of an abnormal immunoglobulin that may be responsible for vasculitis of small‐caliber vessels. Apheresis can be used in order to temporarily eliminate circulating cryoglobulins. The aim of this study was to assess the effectiveness of apheresis (double‐filtration plasmapheresis‐DFPP‐) in symptomatic and/or severe cryoglobulinemias. Methods: Four male patients presenting cryoglobulinemic vasculitis and who received DFPP sessions were included. Results: Their mean age was 57 ± 15 years. One patient had hepatitis‐C virus (HCV)‐related cryoglobulinemia and the other three patients were carriers of an IgM Kappa monoclonal gammopathy. Mean duration of follow‐up was 15 ± 2 months. DFPP allowed healing of ulcerative skin lesions in the first patient and remission of nephrotic syndrome in the other patients after a median of 6(5–10) sessions. Conclusion: DFPP can be used safely in cryoglobulinemic‐vasculitis and can be considered early to achieve a faster and sustained clinical‐biological response.